Mucolytic Activity of Ethanolic Extract of Red Hanjuang Leaves (Cordyline fruticosa L.): An In Vitro Study Using Duck Egg White as a Simulated Mucus Model - Vera Nurviana; Vilsa Purnama; Tresna Lestari (Jurnal Tumbuhan Obat Indonesia, 2025)
Acute respiratory tract infection (ARI) is an infectious condition involving the upper and lower respiratorytract, with one of the symptoms being a cough with phlegm. Conventional treatment usually involves theuse of mucolytic agents such as acetylcysteine and ambroxol. The use of these drugs is reported to havepotential side effects, so alternative herbal-based mucolytic therapy is needed. The purpose of this studywas to evaluate the mucolytic effectiveness of ethanol extract of red hanjuang (Cordyline fruticosa (L.) A.Chev.) leaves. Extraction was performed using the maceration technique with 70% ethanol as the solvent.,with the maceration process directly on pure simplicia, and also on simplicia that had undergone a defattingprocess to obtain ethanol extract of red hanjuang leaves (EEH) and ethanol extract purification of redhanjuang leaves (EEPH). Mucolytic activity was assessed by measuring the viscosity of duck egg white usinga Brookfield viscometer. Acetylcysteine was used as a positive control, while a mixture of duck egg whiteand phosphate buffer at pH 7 served as a negative control. The mucolytic activity of EEH and EEPH wastested at concentrations of 0.5%, 1%, and 1.5%. Data were analyzed using one-way ANOVA followed by theLSD post hoc test. The results indicated that EEH and EEPH possessed mucolytic activities comparable tothe positive control (p > 0.05). Among the tested samples, EEPH at 1% concentration exhibited the strongestmucolytic effect, significantly outperforming the positive control (p < 0.05). Keywords: ARI, Sputum, Mucolytic, Red Hanjuang Leaves, Cordyline fruticosa L.